OVERVIEW OF KNOWLEDGE, GESTATIONAL AGE, EDUCATION, ATTITUDES, AND SOURCES OF INFORMATION FOR PREGNANT WOMEN IN PREPAREDNESS TO FACE FLOOD DISASTERS IN THE WORK AREA OF PUSKESMAS BLANG MANGAT SUB-DISTRICT BLANG MANGAT LHOKSEUMAWE CITY - Nizan Mauyah; Subki Subki; Burdah Burdah (Jurnal Ekonomi, 2023)
This study aims to determine the picture of knowledge, gestational age, education, attitudes, sources of information for pregnant women in preparedness to face flood disasters in the puskesmas work area Blang Mangat. The design of this study is an analytical research with a cross sectional approach. Hasil this study states that, firstly, there is a meaningful relationship between the knowledge of pregnant women and preparedness after the flood disaster at the Blang Mangat Health Center, Lhokseumawe City in 2022. Second, there is no meaningful relationship between gestational age and preparedness during flood disasters at the Blang Mangat Health Center in Lhokseumawe City in 2022. Third, there is a meaningful relationship between pregnant women's education and preparedness during flood disasters at the Blang Mangat Health Center in Lhokseumawe City in 2022. Fourth, there is no meaningful relationship between the attitudes of pregnant women and preparedness after the flood disaster at the Blang Mangat Health Center, Lhokseumawe City, in 2022. And finally, there is no meaningful relationship with disaster preparedness with flood information at the Blang Mangat Health Center in Lhokseumawe City in 2022.